The old rugged Cross : a history of atonement in popular Christian devotion - Pugh, Ben (Eugene, Oregon : Cascade Books, 2016)
A lot has been said about the atonement theology of the theologians, but what of ordinary believers and their church leaders? What, if anything, have they done with'penal substitution'or with'Christus Victor'? How, if at all, have these doctrinal approaches helped ordinary Christians to live more devoted lives or lead good church services? Ben Pugh takes the temperature of the church at various points in its history right up to the present day, noting particular emphases that can be detected in various expressions of personal and corporate faith--whether these be hymns, sermons, magazines, or devotional texts. The book aims not only to describe what the implied atonement theologies of the church have in reality been but also to explore why these have taken the forms that they have. This exploration will shed some fresh light on current debates, building on the findings of the author's earlier work, Atonement Theories: A Way through the Maze.
Description based on print version record.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Atonement -- History of doctrines; Atonement -- History of doctrines; RELIGION -- Christian Theology -- Christology; Electronic books